Penerapan Algoritma AES (Advanced Encryption Standard) Untuk Meningkatkan Keamanan Data Pribadi - Seto, Wahyu (Jurnal Pelita Teknologi, 2024)
Data security is one of the most crucial aspects in today's digital era. When it comes to storing and transmitting personal data, it is highly sensitive, and proper protection is necessary to prevent unauthorized access and potential misuse of information. One effective method to ensure data confidentiality is through the use of strong encryption algorithms, and one internationally recognized encryption algorithm is the Advanced Encryption Standard (AES). The aim of this research is to implement the AES algorithm to enhance the security of personal data. This study will examine and analyze the implementation of AES in an application involving the transmission and storage of personal data. Furthermore, it will involve testing and evaluating the security of the applied AES algorithm. The research methodology employed in this study is research and development.